2004
DOI: 10.1016/j.febslet.2004.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tau mRNA and soluble tau isoforms in affected and non‐affected brain areas in Alzheimer's disease

Abstract: In Alzheimer's disease (AD), selective expression of tau isoforms might underlie the susceptibility of different brain areas to develop neurofibrillary tangles and this pattern might change in the disease. In this study, we have analyzed in control subjects and in sporadic AD patients the pattern of expression of tau mRNA and tau proteins in areas unaffected (cerebellar cortex, white matter), moderately affected (occipital striate cortex, thalamus, caudate nucleus, and putamen) or strongly affected by neurofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 37 publications
5
61
1
Order By: Relevance
“…The finding of increased 3R-tau level in AD brain is inconsistent with previous studies, which showed either an increase in 4R-tau expression in brain regions affected by sporadic AD (15,45) or no change in tau isoforms in AD brain (13,46). Most of these studies detected mRNA levels of 3R-tau and 4R-tau.…”
Section: Discussioncontrasting
confidence: 56%
“…The finding of increased 3R-tau level in AD brain is inconsistent with previous studies, which showed either an increase in 4R-tau expression in brain regions affected by sporadic AD (15,45) or no change in tau isoforms in AD brain (13,46). Most of these studies detected mRNA levels of 3R-tau and 4R-tau.…”
Section: Discussioncontrasting
confidence: 56%
“…The increase of total tau in AD brains (59,60) is not likely caused by up-regulated transcription of tau gene but by an upregulated translation of tau mRNA because tau mRNA copy number is not changed in sporadic AD brains (61,62), and tau mRNA has 5Ј toplike structure that is preferentially regulated by the mTorC1-S6K pathway (36,42). Inhibition of mTor with rapamycin induces a decrease in the level of total tau both in vitro and in vivo (36,43,51).…”
Section: Discussionmentioning
confidence: 99%
“…63,64,212 No difference in the ratio of four-and three-repeat isoforms was found in total postmortem AD brain tau, but a roughly 1.5-fold excess of four-repeat tau has been reported in the temporal cortices of AD brains. 207,213,214 Four-repeat tau binds microtubules with a higher affinity than three-repeat tau, and an isoform imbalance in favor of four-repeat isoforms might impair kinesin-dependent anterograde traffic, because tau and kinesins bind to the microtubule surface in a competitive fashion. 28,30,146 Shifting the tau isoform ratio from fourrepeat to three-repeat isoforms by alternative splicing was therefore proposed as a therapeutic option in tauopathies.…”
Section: Isoform Approachesmentioning
confidence: 99%